Glucagon-like Peptide-1 Receptor Agonists: A New Frontier in Treating Alcohol Use Disorder - Tyler S. Oesterle; Ming-Fen Ho (Brain Sciences)
Background/Objectives: Glucagon-like peptide-1 receptor agonists (GLP-1RAs), which were originally developed for managing type 2 diabetes by enhancing insulin secretion and reducing appetite, have emerged as promising candidates in alcohol use disorder (AUD). These medications offer a dual mechanism of action that aligns with the multifaceted nature of addiction by targeting both peripheral metabolic and central reward pathways. This review focused on the current clinical trials and real-world evidence regarding the effects of GLP-1RAs as novel therapeutics for AUD. We also discussed early but encouraging results from clinical trials in AUD, observational and real-world evidence, safety profiles, psychiatric considerations, and future directions leading beyond GLP-1RAs. Methods: A comprehensive English-language literature search was conducted per PRISMA guidelines across PubMed, Medline, Google Scholar, Web of Science, and trial registries. Using targeted keywords, we identified relevant clinical and observational studies on GLP-1RAs for alcohol use disorder, excluding off-topic or non-English works and assessing all studies for eligibility. Results: Out of 1080 records identified, seven studies met the inclusion criteria. The findings from recent clinical trials, large-scale observational studies, and real-world evidence suggest that GLP-1RAs may significantly reduce alcohol consumption, cravings, and alcohol-related hospitalizations. Their central effect on reward processing, coupled with a generally favorable safety profile, supports their potential therapeutic role beyond metabolic disorders. Conclusions: Emerging evidence positions GLP-1RAs as a promising new pharmacologic approach for managing AUD. Ongoing and future research should prioritize larger, longer-duration randomized controlled trials that include diverse populations, with specific attention to treatment motivation, co-occurring psychiatric conditions, and long-term outcomes.